Implementation of Contextual Teaching and Learning Model on Web-Based Learning Multimedia for Database Subjects - Dini, Nur Amruna; Prabawa, Harsa Wara; Erlangga, Erlangga (Universitas Pendidikan Indonesia, 2021)
Database is one of the important components in an information system because the database will provide information that will be used by the user. Preliminary research reveals information that understanding material regarding Entity Relationship Diagram (ERD) is still difficult for students to understand. Understanding database concepts requires relationships that are based on perceptions in the real world. Contextual Teaching and Learning (CTL) is a learning concept that will help teachers to relate learning material to the actual situation experienced by students. This research uses comparative causal quantitative research and applies the Extensive Lifecycle (ELC) software development method. This research got the following results: 1) Multimedia web-based learning has a percentage of 188.5 with the category